Improving Self Confidence of Students in Mathematics Learning Using Think Pair Share (TPS) Cooperative Model with Worked Example Assisted - Ressy Rustanuarsi (JP2D (Jurnal Penelitian Pendidikan Dasar) UNTAN, 2019)
This study aims to increase the confidence of VII B grade students of SMP Negeri 14 Yogyakarta in learning mathematics through a cooperative learning model of Think Pair Share (TPS) type assisted by working examples. This research is a Classroom Action Research conducted in two cycles. The subjects of this study were students of class VII B of SMP Negeri 14 Yogyakarta in the 2017/2018 academic year consisting of 34 students. The results showed that the students' self-confidence scores in learning mathematics in the first cycle reached 82.36% in the minimally high category. Because these results have not reached the desired target, then proceed with the second cycle. In cycle II, the students' self-confidence scores in learning mathematics reached 88.24% in the minimally high category. It showed that there is an increase in student confidence in learning mathematics through a cooperative learning model type Think Pair Share (TPS) aided by working examples.